Investigation of a new microchip electrophoresis instrument for semi-continuous aerosol composition measurements - Evanoski-Cole, Ashley R., author; Collett, Jeffrey L., advisor; Henry, Charles S., committee member; Kreidenweis, Sonia M., committee member (Colorado State University. Libraries, 2012)
The high variability of atmospheric aerosol composition over both time and space and their importance to the global radiation budget, biogeochemical processes, human health, atmospheric visibility and other important issues has motivated the development of a novel instrument to measure temporal and geographical trends of aerosol composition. The aerosol microchip electrophoresis (ACE) instrument uses a water condensation growth tube to collect water soluble aerosols. Rapid separation and detection of common inorganic ions (chloride, nitrate and sulfate) and one organic acid (oxalate) in the collected aqueous sample is achieved using microchip capillary electrophoresis coupled with conductivity detection. The ACE system was tested in multiple pilot field studies and compared with measurements collected by a particle-into-liquid sampler coupled with an ion chromatograph (PILS-IC) and filter samples. Laboratory tests were also performed with generated aerosol to test the accuracy of ACE. The ACE system has the advantage of being able to achieve fast semi-continuous measurements with time resolution up to one minute. Additionally, the small size footprint and low manufacturing cost make ACE an ideal field instrument to attain rapid and sensitive aerosol composition measurements.